Realistic Kidney Tissue Surrogates for Multienergy Computed Tomography—Feasibility and Estimation of Energy-Dependent Attenuation Thresholds for Renal Lesion Enhancement in Low-kV and Virtual Monoenergetic Imaging. Issue 12 (December 2021) - Euler, André; Zadory, Matthias; Breiding, Philipe Sebastian; Sartoretti, Thomas; Ghafoor, Soleen; Froehlich, Johannes Malta; Donati, Olivio Fabrizio
Abstract : Purpose: The aims of this study were to assess if kidney tissue surrogates (KTSs) are superior to distilled water-iodine solutions in the emulation of energy-dependent computed tomography (CT) attenuation characteristics of renal parenchyma and to estimate attenuation thresholds for definite lesion enhancement for low-kV single-energy and low-keV dual-energy virtual monoenergetic imaging. Methods: A water-filled phantom (diameter, 30 cm) with multiple vials was imaged on a dual-source dual-energy CT (DS-DE) and a single-source split-filter dual-energy CT (SF-DE), both in single-energy mode at 80, 100, 120, 140 kVp and in dual-energy mode at 80/Sn150, 90/Sn150, and 100/Sn150 kVp for DS-DE and AuSn120 kVp for SF-DE. Single-energy images, linear-blended dual-energy images, and virtual monoenergetic imaging at energy levels from 40 to 190 keV were reconstructed. First, attenuation characteristics of KTS in solid and liquid consistencies were compared. Second, solid KTSs were developed to match the CT attenuation of unenhanced renal parenchyma at 120 kVp as retrospectively measured in 100 patients. Third, CT attenuation of KTS-iodine and water-iodine solutions at 8 different iodine concentrations (0–10 mg I/mL) were compared as a function of tube voltage and of keV level using multiple linear regression models. Energy-dependent attenuation thresholds for definite lesion enhancement were calculated. Results: Unenhanced renal parenchyma at 120 kVp measured on average 30 HU on both scanners in the patient cohort. Solid KTS with a water content of 80% emulated the attenuation of unenhanced renal parenchyma (30 HU) more accurately compared with water-iodine solutions (0 HU). Attenuation difference between KTS-iodine and water-iodine solutions converged with increasing iodine concentration and decreasing x-ray energy due to beam-hardening effects. A slight attenuation difference of approximately 2 HU was found between the 2 CT scanners. Attenuation thresholds for definite lesion enhancement were dependent on tube voltage and keV level and ranged from 16.6 to 33.2 HU and 3.2 to 68.3 HU for single-energy and dual-energy CT scan modes for DS-DE and from 16.1 to 34.3 HU and 3.3 to 92.2 HU for SF-DE. Conclusions: Kidney tissue surrogates more accurately emulate the energy-dependent CT attenuation characteristics of renal parenchyma for multienergy CT compared with conventional water-iodine approaches. Energy-dependent thresholds for definite lesion enhancement could facilitate lesion characterization when imaging at different energies than the traditional 120 kVp. Abstract : Supplemental digital content is available in the text.